Corporate Social Responsibility Education in Internal Control and Audit - Dineva, Valeria (Research Papers, 2018)
The present study aims to explore the need to incorporate corporate social responsibility into internal control training and internal audit. There are presented the possibilities for inclusion of the subject in the internal control and audit training, showing different approaches, models and tools. Methods of analysis, secondary analysis, comparative historical method, system analysis method, etc. were used. The results are outlining a wide range of factors that generate needs that require corporate social responsibility to be incorporated into internal control and internal audit training. The conclusion is that corporate social responsibility should be included in the teaching materials and internal control and internal audit programs, and modern concepts and approaches should be applied in training.